The Influence of Globalization and Digitalization on Wage Policy - Muhamad Yosi Agustian; Binsar Jon Vic S (Journal Customary Law, 2026)
Globalization and digitalization have become two major phenomena that affect the dynamics of employment in various countries, including Indonesia. This development brought significant changes in the structure of the labor market, patterns of Labor Relations as well as mechanisms for determining wages. This study aims to analyze the influence of globalization and digitalization on wage policy and its implications for legal protection for workers. The method used is normative legal research with legislation approach and conceptual approach by reviewing various labor related regulations and relevant legal literature. The results show that globalization promotes increased labor competition and job market flexibility, while digitization brings new work models such as the gig economy and platform based work that affect conventional wage systems. This condition has the potential to cause uncertainty and inequality in wages if not balanced with adaptive and responsive policies. Therefore, it is necessary to reformulate wage policies that are able to accommodate global changes and technological developments and still ensure the protection of workers rights in accordance with the principles of justice, legal certainty and social welfare.